Hungarian religion, Romanian blood : a minority's struggle for national belonging, 1920-1945 - Davis, R. Chris (Robert Chris), 1975- (The University of Wisconsin Press, 2018)
Amid the rising nationalism and racial politics that culminated in World War II, European countries wishing to "purify" their nations often forced unwanted populations to migrate. The targeted minorities had few options, but as Chris Davis shows, they sometimes used creative tactics to fight back, redefining their identities to serve their own interests. Davis's highly illuminating example is the case of the little-known Csangos, an ethnic community in Moldavian Romania who practice Catholicism and speak a mix of Hungarian and Romanian. Romania wanted to expel them; Hungary wanted them for resettlement. Aided by Catholic priests, the Csangos resisted deportation with a concerted strategy involving blood samples, anthropologists, and historians, hoping to exempt themselves from the discrimination and violence that targeted Jews, Roma, Slavs, and other minorities. Davis draws on many facets of the Csangos' refashioning to add insight to debates about racial politics, national communities, and ethnic and religious minorities past and present